Small airways dysfunction: the link between allergic rhinitis and allergic asthma. Issue 2 (22nd February 2018) - Haccuria, Amaryllis; Van Muylem, Alain; Malinovschi, Andrei; Doan, Vi; Michils, Alain
Abnormal airway reactivity and overproduction of nitric oxide (NO) occurring in small airways have been found in asthma. If the "one airway, one disease" concept is consistent, such dysfunctions should also be detected in the peripheral airways of patients suffering from allergic rhinitis. We investigated whether peripheral airway reactivity and NO overproduction could be documented in distal airways in patients with allergic rhinitis. Exhaled NO fraction ( F eNO ) and the slope (S) of phase III of the single-breath washout test (SBWT) of helium (He) and sulfur hexafluoride (SF6 ) were measured in 31 patients with allergic asthma, 23 allergic rhinitis patients and 24 controls, before and after sputum induction. SBWT is sensitive to airway calibre change occurring in the lung periphery. The F eNO decrease was more significant in asthma and rhinitis than in controls (−55.1% and −50.0%, respectively, versus −40.8%) (p=0.007 and p=0.029, respectively). SSF6 and SHe increased in all groups. Change in SHe (ΔSHe ) > ΔSSF6 was observed in rhinitis (p=0.004) and asthma (p<0.001), whereas ΔSSF6 = ΔSHe in controls (p=0.431). This study provides evidence of peripheral airway dysfunction in patients with allergic rhinitis quite similar to that described in asthma. Furthermore, a large proportion of the increased NO production reported in allergic rhinitis appears to originate in the peripheral airways. Abnormal airway reactivity and NO production are detected in peripheral airways of patients with allergic rhinitis http://ow.ly/hSwc30hdOm2